Regeneration in a natural population of Araucaria angustifolia (Araucariaceae) Regeneração De Uma População Natural De Araucaria angustifolia (Araucariaceae) - Paludo G.F.* (2011)
Some studies have been suggesting low regeneration capacity in Araucaria angustifolia (Bertol.) Kuntze, based mainly on the small number of regenerating individual. However, there are no works on natural regeneration dynamics. The objective of this work was to study regeneration dynmics of plants in a conservednatural population of A. angustifolia under a developed forest. In a permanent 5.1 ha-plot was installed in the Forest Genetic Reserve of Caçador, state of Santa Catarina. It was evaluated in three consecutive years the regenerating individuals (< 5m tall) and it was discussed the probable factors responsible for found structure. The spatial pattern was analyzed with the Ripley's K Function. It was found variation in the number of ingressing individuals among the evaluated years, as well as for the dead individuals. The critical stage of regeneration of this species appeared in the first years of development 0.5 m of height. Aggregation was predominant in the ingressing individuals and in natural regeneration as a whole. But, because A. angustifolia is a longlived species, it can keep a low number of regenerating individuals in the population and even though succeed in regeneration.